A scoping analysis of Cathelicidin in response to organic dust exposure and related chronic lung illnesses - Golec, Marcin; Lemieszek, Marta Kinga; Dutkiewicz, Jacek; Milanowski, Janusz; Barteit, Sandra (International journal of molecular sciences, 2022)
Over two billion people worldwide are exposed to organic dust, which can cause respiratory disorders. The discovery of the cathelicidin peptide provides novel insights into the lung’s response to organic dust; however, its role in the lung’s response to organic dust exposure and chronic lung diseases remains limited. We conducted a scoping review to map the current evidence on the role of cathelicidin LL-37/CRAMP in response to organic dust exposure and related chronic lung diseases: hypersensitivity pneumonitis (HP), chronic obstructive pulmonary disease (COPD) and asthma. We included a total of n = 53 peer-reviewed articles in this review, following the process of (i) a preliminary screening; (ii) a systematic MEDLINE/PubMed database search; (iii) title, abstract and full-text screening; (iv) data extraction and charting. Cathelicidin levels were shown to be altered in all clinical settings investigated; its pleiotropic function was confirmed. It was found that cathelicidin contributes to maintaining homeostasis and participates in lung injury response and repair, in addition to exerting a positive effect against microbial load and infections. In addition, LL-37 was found to sustain continuous inflammation, increase mucus formation and inhibit microorganisms and corticosteroids. In addition, studies investigated cathelicidin as a treatment modality, such as cathelicidin inhalation in experimental HP, which had positive effects. However, the primary focus of the included articles was on LL-37’s antibacterial effect, leading to the conclusion that the beneficial LL-37 activity has not been adequately examined and that further research is required.